ANALISIS TEKNO-EKONOMI PENERAPAN PLTS OFF-GRID BERBASIS SISTEM DC UNTUK PENERANGAN RUMAH SUBSIDI - Asa Taufiqurrahman; Yohanes Ragil Purnomo; Fadhil Muhammad Nuryanto (Jurnal Elektro Kontrol (ELKON), 2026)
This study analyzes the implementation of a direct current (DC)-based off-grid photovoltaic (PV) system to meet the lighting energy demand of a Type 33/60 subsidized house. The assessment was conducted using a techno-economic approach, including energy demand analysis, system component sizing, performance simulation using PVSyst software, and economic evaluation through the Levelized Cost of Energy (LCOE) and Net Present Cost (NPC) methods. The results indicate that the house lighting system requires 461 Wh/day of energy with a total installed load of 63 W. The proposed system consists of a 160 Wp solar module, a 12 V 180 Ah battery, and a 10 A MPPT solar charge controller (SCC). PVSyst simulation results confirm that the system is capable of supplying an annual energy demand of 168.26 kWh/year, achieving a Solar Fraction of 100% and a Performance Ratio of 59.04%, with no missing energy or loss of load throughout the simulation period. The economic analysis shows an LCOE of IDR 5,236/kWh and an NPC of IDR 11.26 million over a 25-year project lifetime. These findings demonstrate that a DC-based off-grid PV system has significant potential as an independent, efficient, and sustainable energy solution for subsidized housing lighting applications, particularly in areas that are not yet connected to the electricity grid.